Analysis of Online Marketing and Accounting Information in Increasing MSME Competitiveness during the Covid-19 Pandemic - Arum Ardianingsih; Dwi Edi Wibowo (Budapest International Research and Critics University, 2022)
MSME or Micro, Small, and Medium Enterprises have a role as a people`s economic movement that can absorb a lot of labor. Limited economic activity during the covid-19 pandemic led to a decrease in sales turnover for Micro, small and medium enterprises businessmen. So, it necessary to increase the competitiveness MSME`s through the use accounting information and online marketing. This research is descriptive qualitative research. The research object is the MSME`s businessmen in the wholesale market of sentono Pekalongan. Types and sources of data in this study are divided into primary data and secondary data. The research data were obtained through in-depth interviews and documentation. The research data is then reduced, analyzed and conclusion drawn. The results showed that there were still many MSME businessmen who did not understand and had adequate knowledge and understanding of the use of accounting information and online marketing. The use of accounting information is limited to compiling and using cash-in and using cash-out books, to determine the amount of business income and expenses. Meanwhile, the marketing is waiting for consumers to visit their place of sale. Some MSME businessmen have started to switch to online marketing through social media such as WhatsApp, Instagram and Facebook. However, the effectiveness of online marketing through social media has not been done optimally. MSME businessmen need assistance in the use of online accounting and marketing information to support their competitiveness.